2021
DOI: 10.3389/fpsyt.2021.800047
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Comorbid Personality Disorder in Psychotic and Non-psychotic Disorders

Abstract: Introduction: The burden of personality disorders (PDs) in China is large and the focus on mental health services is increasing. However, there is a lack of sufficient evidence regarding the prevalence of comorbid PD in psychotic and non-psychotic disorders, and whether PDs have different distributions. We aimed to investigate the PD comorbidity distribution pattern between psychotic and non-psychotic disorders using a clinical population-based study.Materials and Methods: We conducted a cross-sectional study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…There is no epidemiological data from the existing literature on the specific prevalence of personality disorders. However, some studies have reported 30-50% of CNsMD were co-morbid with personality disorders [30][31][32]. Individuals with mental illness may be at risk of developing personality disorders.…”
Section: Summary Of Findings and Comparison With Existing Literaturementioning
confidence: 99%
“…There is no epidemiological data from the existing literature on the specific prevalence of personality disorders. However, some studies have reported 30-50% of CNsMD were co-morbid with personality disorders [30][31][32]. Individuals with mental illness may be at risk of developing personality disorders.…”
Section: Summary Of Findings and Comparison With Existing Literaturementioning
confidence: 99%
“…Patients suffering from schizophrenia are at higher risk-compared to the general population-of developing physical comorbidities, including cardiovascular diseases, diabetes, obesity, and cancer, with a significant reduction in life expectancy by 15-20 years [3]. Furthermore, patients with schizophrenia often suffer from comorbid mental disorders, including anxiety disorders, with a prevalence rate of 45% [4]; personality disorders, with a prevalence rate of 25% [5]; or substance use disorders, in up to 70% of patients with schizophrenia [6]. Low levels of long-term functional recovery have been reported by patients with schizophrenia, with frequent relapses and voluntary/involuntary hospitalizations.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in DSM-IV, PDs are placed among Axis II disorders in contrast to Axis I disorders (affective, anxious, obsessive-compulsive, etc.). There is strong evidence of high Axis I and Axis II disorder comorbidity [9], as well as high comorbidity of PDs with other medical and biopsychosocial conditions [10,11] and comorbidity within subtypes of PDs and between PD traits [12,13].…”
Section: Introductionmentioning
confidence: 99%